2022
DOI: 10.3389/fonc.2022.831996
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics for the Preoperative Evaluation of Microvascular Invasion in Hepatocellular Carcinoma: A Meta-Analysis

Abstract: BackgroundMicrovascular invasion (MVI) is an independent risk factor for postoperative recurrence of hepatocellular carcinoma (HCC). To perform a meta-analysis to investigate the diagnostic performance of radiomics for the preoperative evaluation of MVI in HCC and the effect of potential factors.Materials and MethodsA systematic literature search was performed in PubMed, Embase, and the Cochrane Library for studies focusing on the preoperative evaluation of MVI in HCC with radiomics methods. Data extraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In addition, we found significant heterogeneity in the pooled sensitivity and specificity. This observation is similar to that in published meta-analyses of diagnostic accuracy using radiomics (49)(50)(51)(52). Although radiomic models help predict the diagnosis of LNM in breast cancer, they involve numerous analysis methods.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we found significant heterogeneity in the pooled sensitivity and specificity. This observation is similar to that in published meta-analyses of diagnostic accuracy using radiomics (49)(50)(51)(52). Although radiomic models help predict the diagnosis of LNM in breast cancer, they involve numerous analysis methods.…”
Section: Discussionsupporting
confidence: 85%
“…The quantitative radiomics features can reflect the microscopic pathological changes of HCC by extracting features from the overall level of the tumor on the basis of conventional imaging images and evaluating the internal heterogeneity of the tumor (34,35). Several previous similar studies have demonstrated that radiomics has high accuracy in evaluating the MVI in HCC; however, all of these studies analyzed CT-, MRI-, and ultrasound-based radiomics (13)(14)(15). This meta-analysis demonstrates that radiomics-based MRI has high diagnostic performance for predicting the MVI of HCC and can be used as a reliable and quantitative method for the non-invasive diagnosis of MVI in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…MRI can also provide better soft-tissue resolution, multiparameters, and more stable features for assessing tumor heterogeneity. Previous similar studies have included CT-, MRI-, and US-combined radiomics original studies (13)(14)(15). Although they made a subgroup analysis of different imaging modalities, the number of MRI-based radiomics studies included was small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing so can describe tumor heterogeneity and reflect the histopathologic grading and prognosis ( 10 , 11 ). Therefore, radiomics can potentially be effective in the preoperative prediction of MVI ( 12 , 13 ). Some studies suggest that liver radiomics is insufficiently mature to routinely integrate into clinical practice ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%